2021
DOI: 10.3390/medsci9040065
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Clinical Outcomes among Patients with COVID-19 and Diabetes

Abstract: Background Diabetes mellitus (DM) is a decisive risk factor for severe illness in coronavirus disease 2019 (COVID-19). India is home to a large number of people with DM, and many of them were infected with COVID-19. It is critical to understand the impact of DM on mortality and other clinical outcomes of COVID-19 infection from this region. Aims The primary objective of our study was to analyze the mortality rate in people with DM infected with COVID-19. The secondary objectives were to assess the effect of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Diabetes mellitus was found to negatively impact most of the outcomes analyzed in our study like hospital stay, ICU admission, and mortality were all adversely influenced by the presence of diabetes among covid-19 patients. In several studies and meta-analyses, also demonstrated consistent association with severe disease and adverse outcomes in COVID-19 infection among diabetes patients [22,23,24,25] . Clinical outcomes are dependent on many other factors including therapies received during hospitalization as well as associated comorbidities.…”
Section: Discussionmentioning
confidence: 69%
“…Diabetes mellitus was found to negatively impact most of the outcomes analyzed in our study like hospital stay, ICU admission, and mortality were all adversely influenced by the presence of diabetes among covid-19 patients. In several studies and meta-analyses, also demonstrated consistent association with severe disease and adverse outcomes in COVID-19 infection among diabetes patients [22,23,24,25] . Clinical outcomes are dependent on many other factors including therapies received during hospitalization as well as associated comorbidities.…”
Section: Discussionmentioning
confidence: 69%
“…Patient age and past medical history like renal disease (CKD), cardiac disease (CAD) have extensively been described as factors influencing disease severity. 30 Laboratory data such as CRP and ferritin 31 are acute phase reactants and have also previously been associated with COVID-19 disease severity. The large and diverse population used in our work strongly supported these findings, and our interpretable LR model coefficients further numerically show their relative importance.…”
Section: Discussionmentioning
confidence: 98%
“…The coronavirus disease 2019 (COVID- 19), caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), was declared a global pandemic by the World Health Organization on March 11 th 2020, affecting millions of people worldwide 1 .…”
Section: Introductionmentioning
confidence: 99%